1302-2002. De Guldensporenslag en zijn nagalm in de moderne tijd - Hoppenbrouwers, P.C.M. (BMGN - Low Countries Historical Review, 2004)
J.F. Verbruggen, R. Falter, 1302. Opstand in Vlaanderen; M. de Bruijn, Ch. Broer, I. Stroucken, Volc te voet. Gevolgen van de Guldensporenslag voor de opkomst van de burgerij in de Noordelijke Nederlanden; P. Trio, D. Heirbaut, D. van den Auweele, Omtrent 1302; R.C. van Caenegem, 1302. Feiten en mythen van de Guldensporenslag; G.H. Nörtemann, Im Spiegelkabinett der Historie. Der Mythos der Schlacht von Kortrijk und die Erfindung Flanderns im 19. Jahrhundert; C. Billen, 1302 Revisité. 1302 Herbekeken 1302-2002. The Battle of the Golden Spurs and its impact on modern times The commemoration, in 2002, of the 700th anniversary of the Battle of the Golden Spurs at Courtray has generated a stream of new books and articles. They shed new light on two quite different aspects of this memorable event which took place on 11 July 1302: First, the transformation of the battle into a veritable lieu de mémoire; second, the interpretation of the event itself through a more sophisticated explanation of its underlying causes and wider impact, as well as alternative views about the military action that took place. What makes the first aspect so very fascinating is the fact that the myth of 1302 eventually turned into a battlefield itself, where Flemish and Belgian nationalists sat face-to-face, and where three of the overarching ideologies of the nineteenth century — Liberalism, Christian denominationalism, and Socialism — collided. The pacifying tendency among most Belgian national politicians and professional historians, as well as the gradual appropriation of the myth of 1302 by Flemish nationalists, hampered and complicated its transformation into a collective ‘place of remembrance’ acceptable to all Belgians. One conclusion regarding the second aspect is that recent authors have great difficulty escaping the dominant models of interpretation of Moke/Pirenne in the social and economic field, and Verbruggen in the field of military tactics.